Binding of Trivalent Arsenic onto the Tetrahedral au20 and au19pt Clusters: Implications in Adsorption and Sensing - Oyarzun-Medina, M; Oyarzun-Medina, M (American Chemical Society, 2015)
The interaction of arsenic(III) onto the tetrahedral Au20 cluster was studied computationally to get insights into the interaction of arsenic traces (presented in polluted waters) onto embedded electrodes with gold nanostructures. Pollutant interactions onto the vertex, edge, or inner gold atoms of Au20 were observed to have a covalent character by forming metal-arsenic or metal-oxygen bonding, with adsorption energies ranging from 0.5 to 0.8 eV, even with a stable physisorption; however, in aqueous media, the Au-vertex-pollutant interaction was found to be disadvantageous. The substituent effect of a platinum atom onto the Au20 cluster was evaluated to get insights into the changes in the adsorption and electronic properties of the adsorbent-adsorbate systems due to chemical doping. It was found that the dopant atom increases both the metal-pollutant adsorption energy and stability onto the support in a water media for all interaction modes; adsorption energies were found to be in a range of 0.6 to 1.8 eV. All interactions were determined to be accompanied by electron transfer as well as changes in the local reactivity that determine the amount of transferred charge and a decrease in the HOMO-LUMO energy gap with respect to the isolated substrate (Figure Presented). © 2015 American Chemical Society.